Rice and Bean Targets for Biofortification Combined with High Carotenoid Content Crops Regulate Transcriptional Mechanisms Increasing Iron Bioavailability - Dias, Desirrê Morais (Nutrients, 2015)
Iron deficiency affects thousands of people worldwide. Biofortification of staple food crops aims to support the reduction of this deficiency. This study evaluates the effect of combinations of common beans and rice, targets for biofortification, with high carotenoid content crops on the iron bioavailability, protein gene expression, and antioxidant effect. Iron bioavailability was measured by the depletion/repletion method. Seven groups were tested (n = 7): Pontal bean (PB); rice + Pontal bean (R + BP); Pontal bean + sweet potato (PB + SP); Pontal bean + pumpkin (PB + P); Pontal bean + rice + sweet potato (PB + R + P); Pontal bean + rice + sweet potato (PB + R + SP); positive control (Ferrous Sulfate). The evaluations included: hemoglobin gain, hemoglobin regeneration efficiency (HRE), gene expression of divalente metal transporter 1 (DMT-1), duodenal citocromo B (DcytB), ferroportin, hephaestin, transferrin and ferritin and total plasma antioxidant capacity (TAC). The test groups, except the PB, showed higher HRE (p < 0.05) than the control. Gene expression of DMT-1, DcytB and ferroportin increased (p < 0.05) in the groups fed with high content carotenoid crops (sweet potato or pumpkin). The PB group presented lower (p < 0.05) TAC than the other groups. The combination of rice and common beans, and those with high carotenoid content crops increased protein gene expression, increasing the iron bioavailability and antioxidant capacity.